Investigation of the situations affecting vocational school students’ anxiety levels and academic achievements - Bayraktar, Muhammet; Doğan, Mehmet (The European Research Journal, 2021)
Objectives: In this study, we aim to determine the prevalence of anxiety and evaluate its relationship with academic performance in a vocational school of health services students, which causes significant disability and loss of labor and is frequently seen with mood disorders in the society. Methods: A sample was not selected for the research, it was aimed to reach all students. Of the 1093 students who are attending the school, 849 (77.7%) students participated in the study. In order to determine the level of anxiety in students, a questionnaire form consisting of the Beck Anxiety Inventory and descriptive features were applied by the online survey method. Results: Of the students; 80.1% are female, 98.1% are single, 57.1% are in their first year, and the average age is 20.25 ± 1.81. The total scale score was found 9.42 ± 8.65 and it was 9.90 ± 8.69 for female students and 7.49 ± 8.24 for male students. Variable levels of anxiety were detected in 38.8% of the participants. There was no statistically significant relation found between anxiety level and academic performance, but both anxiety levels and academic performances were affected by the gender of participants. Conclusions: Making psychological evaluations of students while they are starting their higher education and checking their statuses periodically using standard self-report tools by using technological instruments; would make it possible to make necessary interventions by noticing the situations that may adversely affect their academic success, social life, mental and cognitive development in the early stages.